Detecting Text Similarity Using MapReduce Framework - Birjali, Marouane; Beni-Hssane, Abderrahim; Erritali, Mohammed; Madani, Youness (Europe and MENA Cooperation Advances in Information and Communication Technologies, 2016)
The evaluation of similarities between textual documents was regarded as a subject of research strongly recommended in various domains. There are many of documents in a large amount of corpus. Most of them are required to check the similarity for validation. In this paper, we propose a new MapReduce algorithm of document similarity measures. Then we study the state of the art of different approaches for computing the similarity of amount documents to choose the approach that will be used in our MapReduce algorithm. Therefore, we present how the similarity between terms is used in the assessment of the similarity between documents. Simulation results, on Hadoop framework, show that our MapReduce algorithm outperforms classical ones in term of running time.